Reconstructing high resolution environmental change from carbonate-rich lakes in Turkey and Mexico using varve microfacies analysis - Primmer, Nick (2019)
Analysis of lacustrine sediment records provide insight into terrestrial environmental change throughout the Holocene; however, poor chronological control often limits a record’s ability to identify the precise dynamics and drivers of these changes. Exploring these important aspects of environmental change can develop our understanding of the mechanisms driving long-term climatology and its influence on regional hydrological systems. To fully investigate these past environmental systems, high resolution, climatically-sensitive proxies are required.